1983
DOI: 10.1002/1097-4679(198301)39:1<114::aid-jclp2270390122>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in symbol-digit substitution task performance

Abstract: A decline in performance on the Digit Symbol Substitution test related to aging is well documented. There is no agreement on the reason for the decline, however. In part, the lack of consensus with regard to changes on the test may be attributed to the limitations imposed by comparing groups on a single performance measure. In the present study, three forms of a Symbol‐Digit Substitution task that varied in difficulty level were administered to 125 persons between the ages of 30 and 92. On all forms there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
31
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 32 publications
10
31
0
Order By: Relevance
“…As noted above, the ESS of a symbol has been shown to affect several informationprocessing components, including encoding speed and memory. The manipulation of this variable does affect substitution task performance (Gilmore, Royer, & Gruhn, 1983;Royer, 1971b;Royer, Gilmore, & Gruhn, 1981) but the independent contributions of feature composition and visual confusability to the dramatic influence of ESS have not been assessed. Indeed, in previous investigations by Royer et al the visual confusability and the ESS of the symbols have been confounded.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…As noted above, the ESS of a symbol has been shown to affect several informationprocessing components, including encoding speed and memory. The manipulation of this variable does affect substitution task performance (Gilmore, Royer, & Gruhn, 1983;Royer, 1971b;Royer, Gilmore, & Gruhn, 1981) but the independent contributions of feature composition and visual confusability to the dramatic influence of ESS have not been assessed. Indeed, in previous investigations by Royer et al the visual confusability and the ESS of the symbols have been confounded.…”
Section: Introductionsupporting
confidence: 83%
“…Royer et al have reported differences in symbol-digit substitution task performance between groups classified by gender (Royer, 1978), severity of schizophrenia (Royer & Janowitch, 1973), and age (Gilmore et al, 1983) that are similar in pattern to that reported here for the good and poor search groups. Those studies used multiform substitution tasks in which the symbols were varied across forms according to the ESS of the symbols.…”
Section: Discussionmentioning
confidence: 99%
“…Stein (1962) found that there was no significant sex difference. However, the effect of age was noted in research that used a similar test, Symbol Digit from the WAIS (Gilmore, Royer, & Gruh, 1983). Such a general decline in psychomotor ability has been well documented by others (Bak & Greene, 1980;Bayley, 1968;Horn & Cattell, 1966).…”
Section: Minute Estimation Average Of Trialsmentioning
confidence: 99%
“…Some research has suggested that gender also has an impact (Jorm, Anstey, Christensen, & Rodgers, 2004), though other studies have found no difference (Gilmore, Royer, & Gruhn, 1983). Level of acculturation in an African American sample was found to affect scores on the written version (Kennepohl, Shore, & Nabors, 2004).…”
Section: Symbol Digit Modalities Test (Sdmt)mentioning
confidence: 99%